(untitled) - McCarter, Sam (Thành phố Hồ Chí Minh, 2014)
The book is aimed at those candidates aiming to achieve a Band Score of 6 or more in the Academic Writing component in IELTS. The book contains six sections: Section I: Writing Practice for Task I; Section 2: Witing Practice for Task 2; Section 3: Checking and Editing; Section 4: Practice Writing Tests
Keywords: English language,Anh ngữ thực hành; Writing,Viết